EFEITOS DOS AGROTÓXICOS SOBRE A SAÚDE HUMANA: PESQUISA BIBLIOGRÁFICA - Kusiack, Adriana; Nonnenmacher, Carine L.; Ubessi, Liamara D.; Silva, Luiz A. A. d.; Stumm, Eniva M. F. (Salão do Conhecimento, 2013)
Resumo